Respuesta :

If [tex]x+a[/tex] is a factor of the polynomial, it means that [tex]-a[/tex] is a root of the polynomial.

In fact, if a polynomial [tex]p(x)[/tex] has a root [tex]x_0[/tex] (i.e. [tex]p(x_0)=0[/tex]), then the polynomial is divisible by [tex](x-x_0)[/tex]

In your case, you know that the polynomial is divisible by [tex](x+a)=(x-(-a))[/tex], so [tex]-a[/tex] is a solution.

Let's evaluate [tex]p(-a)[/tex] and set it to zero:

[tex]2(-a)^2+2a(-a)+5(-a)+10 = 0 \iff 2a^2-2a^2-5a+10=0 \iff -5a+10 = 0 \iff a = 2 [/tex]

We can check the answer: if [tex]a=2[/tex] the polynomial becomes

[tex]2x^2+2(2)x+5x+10 = 2x^2+9x+10[/tex]

And we're claiming that [tex]-a=-2[/tex] is a root of this polynomial:

[tex]2(-2)^2+9(-2)+10 = 2\cdot 4 - 18 + 10 = 0[/tex]

ACCESS MORE